Construction of 5-Amino-1,2-Selenazole Scaffolds through N-Selenocyanation/Cyclization of Enaminones Using KSeCN - Yuan, Caifeng; Huang, Xuankun; Guo, Jianhua; Shen, Yiwen; Shang, Na; Tang, Qilin; Yang, Jing; Huang, Yi; Zhang, Hongbin; Tang, E. (Organic letters, 2024)
A metal-free and mild approach for constructing 5-amino-1,2-selenazole skeletons by NBS/KSeCN-mediated N-selenocyanation and nucleophilic cyclization of beta-enaminones has been developed. Various isoselenazole compounds and the isoselenazolyl derivatives of anti-inflammatory medicines, including isosepac, oxaprozin, and ibuprofen, have been obtained with good yields. This efficient, "one-pot", and atomic economy strategy may represent an alternative route for the construction of a 1,2-selenazole framework via the "+SeCN" pathway and provide new access to heterocycles containing a Se-N bond.